PENGARUH VIDEO EDUKASI TERHADAP PENGETAHUAN IBU TENTANG ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS KARYA WANITA - Siti Halimah; Wan Anita; Tharra Widadari Aldinda; Ummu Luthfiyah; Ega Pratiwi (Ensiklopedia of Journal, 2026)
Exclusive breastfeeding is an important factor in supporting the growth and development of infants, but there are still many mothers who do not have adequate knowledge about the benefits and importance of exclusive breastfeeding. Educational efforts through video media are expected to be an effective means of increasing the understanding of breastfeeding mothers. This study aims to determine the effect of education videos on mothers' knowledge about exclusive breastfeeding in the Karya Wanita Health Center working area. The type of research used is quantitative with a Quasi Experiment design using the One Group Pretest-Posttest design. This research was conducted from March to June 2025. The study population amounted to 143 respondents and the research sample amounted to 59 respondents of breastfeeding mothers who had babies aged 0-6 months, selected using purposive sampling technique. The research instrument was a knowledge questionnaire about exclusive breastfeeding and data analysis was carried out with the Wilcoxon test. The results showed an increase in the mother's knowledge score before and after being given an educational video, with a p-value of 0.0010.05 which means there is an effect of educational videos on maternal knowledge about exclusive breastfeeding. The conclusion of this study is that educational videos are proven effective in increasing the knowledge of breastfeeding mothers about exclusive breastfeeding, so it is hoped that health workers can utilize audio-visual media as a means of counseling to support the success of the exclusive breastfeeding program in the community.Keywords: Exclusive Breastfeeding, Knowledge, Educational Videos